Development of an extended 2D porcine muscle cell culture system and impact of growth promoters on muscle’s innate immune resistance - Sebastian, Sujith (2016)
Skeletal muscle comprises about half of the body weight in mammals and its diverse roles in metabolism and innate immune functions makes cultured muscle as a useful tool in biomedical research. In this thesis, some of the major technical obstacles in porcine primary muscle cell cultures such as inadequate differentiation of myoblasts into myotubes and the premature detachment of the formed myotubes have been overcome with the achievement of high differentiation and myotube fusion rate of over 85% along with prolonged maintenance of myotubes in excess of 70 days. Myosin heavy chain (MyHC) expression profile of differentiated myotubes recapitulated adult muscle fibres and displayed phenotypic plasticity of gene expression in response to different media. Growth factor ractopamine (Ract) treatment (1h and 6h) of myotubes followed with subsequent bioinformatics analysis of a stable isotope labelling by amino acids in cell culture (SILAC) based proteomics study suggested differential expression of proteins associated with anti-viral innate immune response and increased protein accretion. Porcine muscle cells were infected with influenza A viruses to evaluate their immune function. Porcine muscle cells expressed influenza virus sialic acid α-2,3 and α-2,6 receptors and were fully permissive to influenza virus infection. Myoblasts produced more virus particles than myotubes. Muscle cells expressed the pro-inflammatory genes tumor necrosis factor alpha (TNF-α) and antiviral gene Mx-1 and the infected cells had elevated caspase 3/7 activity to indicate apoptosis. However, myotubes pre-treated with Ract appeared to confer no reduction in influenza virus output. Evidence presented herein suggests that the functional myotubes developed by this work can be used as a tool to study the molecular mechanisms of growth and innate immune pathways in muscle.